Dissociation of native casein micelles induced by sodium caseinate. (July 2015) - Thomar, Peggy; Nicolai, Taco
Abstract: The effect of addition of sodium caseinate (NaCas) to aqueous solutions of casein micelles was studied at pH 6.7. Addition of NaCas leads to reduction of the turbidity and to a decrease of the fraction of proteins that precipitates during ultracentrifugation. The calcium and orthophosphate concentrations in the supernatant were found to increase with increasing NaCas concentration. The results show that addition of NaCas causes release of colloidal calcium phosphate and dissociation of native caseine micelles. The process is controlled by the weight fraction of NaCas in the mixture and dissociation is complete when the fraction exceeds 75%. The efficacy of NaCas as chelating agent for casein micelles is compared with that of polyphosphate reported in the literature. The liberated calcium and orthophosphate are bound to the added NaCas, which leads to aggregation at higher casein concentrations. Graphical abstract: Highlights: Addition of sodium caseinate drives dissociation of native casein micelles. Dissociation of micelles induced by NaCas is an 'all or nothing' process. Dissociation of micelles starts above 50 wt% NaCas and is complete above 75 wt%. The calcium and phosphate released from the micelles drives aggregation of caseins. Chelation potential of phosphoserines of NaCas is close to that of polyphosphate.